Wild, Native, or Pure: Trout as Genetic Bodies. (November 2021) - Havlick, David G.; Biermann, Christine
Advances in genetics and genomics have raised new questions in trout restoration and management, specifically about species identity and purity, which fish to value, and where these fish belong. This paper examines how this molecular turn in fisheries management is influencing wild and native trout policy in Colorado. Examples from two small Colorado watersheds, Bear Creek and Sand Creek, illustrate how framing trout as genetic bodies can guide managers to care for or kill trout populations in the interest of rectifying decades of genetic disruption caused by human activity. While trout management has typically relied on human intervention, the turn to genetic science is prompting new classifications of lineage and taxa, altering long-standing conservation priorities, and reorienting the manipulation of biological processes such as reproduction and dispersal. As a result, other social and ecological factors may be pushed to the margins of management decisions. These changes warrant greater conversation about the consequences of molecular analyses and the values embedded in trout science and conservation more broadly.